Noninvasive ventilation improves the outcome in patients with pneumonia-associated respiratory failure: Systematic review and meta-analysis. Issue 3 (March 2022) - Ruzsics, Istvan; Matrai, Peter; Hegyi, Peter; Nemeth, David; Tenk, Judit; Csenkey, Alexandra; Eross, Balint; Varga, Gabor; Balasko, Marta; Petervari, Erika; Veres, Gabor; Sepp, Robert; et al.
Abstract: Background: Noninvasive ventilation (NIV) is beneficial in exacerbations of chronic obstructive pulmonary disease (COPD), but its effectiveness in pneumonia-associated respiratory failure is still controversial. In the current meta-analysis, we aimed to investigate whether the use of NIV before intubation in pneumonia improves the mortality and intubation rates of respiratory failure as compared to no use of NIV in adults. Methods: We searched three databases from inception to December 2019. We included studies, in which pneumonia patients were randomized initially into either NIV-treated or non-NIV-treated groups. Five full-text publications, including 121 patients, reported eligible data for statistical analysis. Results: With NIV the overall hospital mortality rate seemed lower in patients with pneumonia-associated respiratory failure, but this was not significant [odds ratio (OR) = 0.39; 95% confidence interval (CI): 0.13–1.14; P = 0.085]. In the intensive care unit, the mortality was significantly lower when NIV was applied compared to no NIV treatment (OR = 0.22; 95% CI: 0.07–0.75; P = 0.015). NIV also decreased mortality compared to no NIV in patient groups, which did not exclude patients with COPD (OR = 0.25; 95% CI: 0.08–0.74; P = 0.013). The need for intubation was significantly reduced in NIV-treated patients (OR = 0.22; 95% CI: 0.09–0.53; P = 0.001), which effect was more prominent in pneumonia patient groups not excluding patients with pre-existing COPD (OR = 0.13; 95% CI: 0.03–0.46; P = 0.002). Conclusion: NIV markedly decreases the death rate in the intensive care unit and reduces the need for intubation in patients with pneumonia-associated respiratory failure. The beneficial effects of NIV seem more pronounced in populations that include patients with COPD. Our findings suggest that NIV should be considered in the therapeutic guidelines of pneumonia, given that future clinical trials confirm the results of our meta-analysis. Availability of data and materials: All data and materials generated during the current study are available from the corresponding author on reasonable request.